High prevalence of drink-driving in Thailand - Virasakdi Chongsuvivatwong (2018)
This study was conducted to measure the prevalence of drivers with a blood alcohol concentration (BAC) over 50mg/dl and to identify predictors for such an outcome. A cross-sectional study was conducted during March to August 1995 in eight provinces in Thailand. In each province, with the collaboration of the police, one checkpoint in a suburban area and one on a highway were used to collect data on drivers of 20 motorcycles, 20 4-wheel and 20 6 + -wheel motor vehicles, during 1300-1500h, 1700-1900h and 2200-2400h. For each subject, a breath test for alcohol was undertaken using standard breath testing instruments. Four thousand, six hundred and seventy-five male drivers were tested. The crude prevalence of high BAC was 12.6% (range 4.5-23.7%). The differences in prevalence between the suburban area (8.7%) and the highway (8.4%) and between drivers tested on weekdays (9.8%) and on holidays (7.5%) were not statistically significant. The crude prevalences were 3.4-3.8% and 3.8-3.9% at 1300-1500h and 1700-1900h, respectiveiy. During 2200-2400h the prevalence rose to 19.2%, 16.0% and 11.9% among the motorcyclists, the 4-wheel vehicle drivers and the 6 + -wheel vehicle drivers, respectively. High BAC among Thai drivers in the study period was very common, especially at night. Efforts should be focused on these high-risk groups and this time period.